High-efficiency negative-carbon emission power generation from integrated solid-oxide fuel cell and calciner - Hanak, Dawid P.; Jenkins, Barrie G.; Kruger, Tim; Manovic, Vasilije (Elsevier, 2017)
Direct air capture of CO2 has the potential to help meet the ambitious environmental targets established by the Paris Agreement. This study assessed the techno-economic feasibility of a process for simultaneous power generation and CO2 removal from the air using solid sorbents. The process uses a solid-oxide fuel cell to convert the chemical energy of fuel to electricity and high-grade heat, the latter of which can be utilised to calcine a carbonate material that, in turn, can remove CO2 from the air. The proposed process was shown to operate with a net thermal efficiency of 43.7–47.7%LHV and to have the potential to remove 463.5–882.3 gCO2/kWelh, depending on the fresh material used in the calciner. Importantly, the estimated capital cost of the proposed process (1397.9–1740.5 £/kWel,gross) was found to be lower than that for other low-carbon emission power generation systems using fossil fuels. The proposed process was also shown to achieve a levelised cost of electricity of 50 £/MWelh, which is competitive with other low-carbon power generation technologies, for a carbon tax varying between 39.2 and 74.9 £/tCO2. Such figure associated with the levelised cost of CO2 capture from air is lower than for other direct air concepts.
Keywords: Direct air capture; Solid-oxide fuel cell; Power generation; Process modelling and simulation; Feasibility study; Techno-economic analysis